Development of the Concept the Sinabung Art Festival Event in Improving the Economy of the People of Kuta Gugung Village, Karo Regency. - daryana, Aditiya pratama; Damanik, M. A. Jaya (Politeknik Pariwisata NHI Bandung, 2025)
This study aims to examine the development of the Sinabung Art Festival as an instrument for improving the community's economy and strengthening community capacity in Kuta Gugung Village, Karo Regency, an area affected by the eruption of Mount Sinabung. This festival was initiated as a response to the socio-economic recovery needs of the community after the disaster, by integrating elements of culture, local creativity, and disaster education. The research approach used is qualitative descriptive with a case study method. Data was obtained through in-depth interviews, participatory observations, documentation, and focus group discussions (FGDs), with key informants including MSME actors, festival committees, traditional leaders, visitors, and village officials. The results of the study show that the Sinabung Art Festival significantly contributes to an increase in the income of MSME actors by 200-300% during the festival. In addition, the level of participation of the local community is very high, both in the form of committees, art performances, and educational activities. The festival has also succeeded in becoming a medium for promoting authentic Karo culture and a means of disaster education through documentary exhibitions, lava tours, and evacuation simulations. This study concludes that the Sinabung Art Festival is not just an entertainment event, but a means of sustainable community development that is multidimensional—economic, social, cultural, and educational. The strategic recommendations produced include strengthening the capacity of MSMEs, digitizing promotions, planning annual event calendars, integrating disaster education in tourism, and establishing village-based committee institutions. This research contributes to the development of a post-disaster community-based event model that can be replicated in other areas with similar characteristics. Follow-up studies are recommended to develop socio-cultural and economic sustainability indicators in the context of local festivals.